THE ROLE OF DIGITAL TECHNOLOGIES IN THE ECONOMIC DEVELOPMENT OF CLUSTERS IN AGRICULTURE (World Economics and Finance Bulletin, 2024)
The article examines the effectiveness of investments in innovative activities in agriculture and ways to evaluate it and increase the economic efficiency of its use.
Keywords: relevance of innovative technologies; implemented investments; technological innovations